Glenn Gould: Hereafter - Monsaingeon, Bruno (Ideale audience, 2006)
Product DescriptionA retrospective of the life and work of Glenn Gould, Hereafter synthesizes an incredible wealth of archival material from various sources, some of it previously unreleased. Made as if narrated by Gould himself, Hereafter is a fantastic window opened to the world of a true musical genius, whose magic touches us from beyond the grave. The DVD contains a 20 page booklet with an authoritative essay by the director, a biography and the complete music tracks included in the film.Amazon.comGlenn Gould remains an enigmatic, fascinating figure more than two decades after his death. This new film, directed by Gould's friend Bruno Monsaingeon, who has already written four books and made a 23-part TV series about him, is something very special. Taken from Gould's own words, the pianist himself seems to act as narrator in a retrospective on his life and art. A great deal of archival footage of both interviews and performances exemplify the pianist's genius and eccentricities. There are modern-day interviews as well. One with an Italian woman who comes to hang out with a sculpture of Gould in front of the CBC building in Toronto lets us in on the emotional effect he had on people, and many others discuss how he changed their perceptions of music. Gould himself is remarkably insightful in interviews. He seems to have been a man incapable of being boring or thoughtless. And, of course, the music speaks for itself. You'll hear some of the most stunning playing. Even those of us who already know and appreciate Gould will find new things here. This film is an eye- and ear-opening delight. --Robert LevineReviewA vast legacy remains on (this) disc of the strengths, the originality - and, indeed, the occasional maddening wrong-headedness - of Gould's musical thinking. -- LA Weekly, July 4th 2007